Micromonospora pelagivivens sp. nov., a new species of the genus Micromonospora isolated from deep-sea sediment in Japan. Issue 5 (30th March 2020) - Intra, Bungonsiri; Panbangred, Watanalai; Inahashi, Yuki; Také, Akira; Mori, Mihoko; Ōmura, Satoshi; Matsumoto, Atsuko
Abstract : A novel marine actinomycete, designated strain KJ-029 T, was isolated from a marine sediment sample (water depth of 226 m) in Kagoshima, Japan. 16S rRNA gene sequence analysis revealed that the new isolate was most closely related to Micromonospora craniellae LHW 63014 T (99.3 % similarity). Phylogenetic analyses of the genus Micromonospora based on 16S rRNA gene sequences showed that strain KJ-029 T was clustered with Micromonospora craniellae LHW 63014 T and Micromonospora endophytica 202201 T . However, digital DNA–DNA hybridization analyses presented low levels of relatedness in the range of 24.8–32.9 % between strain KJ-029 T and the above closely related strains. The novel strain contained meso -diaminopimelic acid and 3-OH-diaminopimelic acid, d -glutamic acid, glycine and d -alanine in the cell-wall peptidoglycan. The acyl type of the peptidoglycan was glycolyl and mycolic acids were absent. The major menaquinone was MK-9(H4 ). The whole-cell sugars consisted of glucose, mannose, xylose and ribose. Phosphatidylethanolamine was detected as the major phospholipid and corresponded to phospholipid type II. The predominant cellular fatty acid was iso-C16 : 0 . The DNA G+C content of the genomic DNA was 71.5 mol%. Based on the present polyphasic study, strain KJ-029 T represents a novel species of the genus Micromonospora, for which the name Micromonospora pelagivivens sp. nov. is proposed. The type strain is KJ-029 T (=NBRC 113519 T =TBRC 9233 T ).